2011
DOI: 10.1002/cphc.201100556
|View full text |Cite
|
Sign up to set email alerts
|

Thermal‐Transport Studies on Two‐Dimensional Quantum Spin Liquids

Abstract: Quantum spin liquids (QSLs) are fluidlike states of quantum spins in which the long-range ordered state is destroyed by quantum fluctuations. The ground state of QSLs and their exotic phenomena, which have been extensively discussed for decades, have yet to be identified. We employ thermal-transport measurements on newly discovered QSL candidates κ-(BEDT-TTF)(2)Cu(2)(CN)(3) and EtMe(3)Sb[Pd(dmit)(2)](2), and report that the two organic insulators have different QSLs characterized by different elementary excita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 43 publications
5
44
0
Order By: Relevance
“…It is seen from both Figs. 13 and 14, that our calculations are in good overall agreement with the experimental facts and there is no need to suppose the existence of additional magnetic excitations activated by the application of magnetic field in order to explain the growth of I(B, T ) at elevated B [50,51]. Important signature of electron liquid in HF metals is excitations -quasiparticles carrying electron quantum numbers and characterized by the effective mass M * mag .…”
Section: Quantum Spin Liquidsupporting
confidence: 73%
See 1 more Smart Citation
“…It is seen from both Figs. 13 and 14, that our calculations are in good overall agreement with the experimental facts and there is no need to suppose the existence of additional magnetic excitations activated by the application of magnetic field in order to explain the growth of I(B, T ) at elevated B [50,51]. Important signature of electron liquid in HF metals is excitations -quasiparticles carrying electron quantum numbers and characterized by the effective mass M * mag .…”
Section: Quantum Spin Liquidsupporting
confidence: 73%
“…Recent measurements of κ(B) on the organic insulators EtMe 3 Sb[Pd(dmit) 2 ] 2 and κ−(BEDT−TTF) 2 Cu 2 (CN) 3 [50,51] are displayed in Figs. 13 and 14.…”
Section: Quantum Spin Liquidmentioning
confidence: 99%
“…The obtained dependence at low temperatures rep-1 sembles that of the spin-lattice relaxation rate (1/T 1 T ) at fixed temperature as a function of magnetic field [7]: k(B) at low fields is insensitive to B, displaying a response to increasing magnetic field B. On the other hand, it is suggested that the observed B-dependence implies that some spin-gaplike excitations coupling to the magnetic field are also present at low temperatures [4,5]. As a result, we face a challenging problem of interpretation of the experimental data in a consistent way, including the B-dependence of the heat conductivity.…”
mentioning
confidence: 99%
“…17.9 and 17.16. 3 have two-dimensional triangular lattices with the geometric frustration that prohibits spin ordering even at the lowest accessible temperatures T [42][43][44][45][46]. Therefore, being different form ZnCu 3 (OH) 6 Cl 2 , these insulators offer unique insights into the physics of quantum spin liquids (QSL).…”
Section: Spin-lattice Relaxation Rate Of Quantum Spin Liquidmentioning
confidence: 99%
“…For example, at T → 0 the residual value in κ/T signals that the excitation spectrum is gapless. The presence of the residual value is clearly resolved in EtMe 3 Sb[Pd(dmit) 2 ] 2 , while measurements of κ/T on κ − (BEDT − TTF) 2 Cu 2 (CN) 3 suggest that the low-energy excitation spectrum can have a gap [45,46]. Taking into account the observed T -linear term of the heat capacity in κ − (BEDT − TTF) 2 Cu 2 (CN) 3 with the static spin susceptibility remaining finite down to the lowest measured temperatures [47], the presence of a gap in the spin excitation becomes questionable.…”
Section: Spin-lattice Relaxation Rate Of Quantum Spin Liquidmentioning
confidence: 99%